2018
DOI: 10.1039/c7ra13011b
|View full text |Cite
|
Sign up to set email alerts
|

Colon-targeting mutual prodrugs of 5-aminosalicylic acid and butyrate for the treatment of ulcerative colitis

Abstract: The aim of this study was to design and synthesize four colon-targeting mutual prodrugs of 5-aminosalicylic acid (5-ASA) and butyrate, and evaluate their therapeutic effects on ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…According to these physiological characteristics, traditional drug delivery systems based on colonic physiological characteristics, such as pH-dependent 17 , time-dependent 18 , and pressure-controlled 19 , have been proposed. In addition, passive targeting drug delivery systems initiated by microbial flora, such as enzyme-triggered 20 , prodrug delivery systems 21 , enzyme-degradable polymer-coated drug delivery systems 22 , and complex colon targeting drug delivery systems 23 , which combine several delivery systems, are used. In the field of drug carrier materials, chemical modification of carrier materials or carrier materials with strong sensitivity and specificity, stable drug release process, and nontoxic side effects is currently a research hotspot in this field.…”
Section: Advantages and Development Of Oral Colon-targeted Drug Delivmentioning
confidence: 99%
“…According to these physiological characteristics, traditional drug delivery systems based on colonic physiological characteristics, such as pH-dependent 17 , time-dependent 18 , and pressure-controlled 19 , have been proposed. In addition, passive targeting drug delivery systems initiated by microbial flora, such as enzyme-triggered 20 , prodrug delivery systems 21 , enzyme-degradable polymer-coated drug delivery systems 22 , and complex colon targeting drug delivery systems 23 , which combine several delivery systems, are used. In the field of drug carrier materials, chemical modification of carrier materials or carrier materials with strong sensitivity and specificity, stable drug release process, and nontoxic side effects is currently a research hotspot in this field.…”
Section: Advantages and Development Of Oral Colon-targeted Drug Delivmentioning
confidence: 99%
“…The in vitro release studies of all colon-targeted prodrugs 9 and 20a–20g were further carried out in a colon-content suspension (the colonic segment of the rat intestines was cut, and its contents were suspended to prepare the colon content suspension) at 37 °C from 0 to 5 h. , Sulfasalazine was used as a positive control to verify the activity of azo reductase in the colon content suspension (Figure A). Considering that the clinical studies showed that the oral therapeutic dose of olsalazine (colon-specific azo prodrug of 5-ASA) was much higher than that of tofacitinib (olsalazine and tofacitinib:1000 mg once daily and 5 mg twice daily, respectively), , the release exposures of 5-ASA from prodrugs were not tested in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H and 13 C NMR spectra were recorded in d 6 DMSO. The 1 H NMR spectrum of the ligand exhibits two signals that appeared at 9.45 and 8.25 ppm belong to protons of COOH and phenolic OH groups, [ 35 ] respectively. The signal at 5.65 ppm corresponds to the –NH 2 protons.…”
Section: Resultsmentioning
confidence: 99%
“…that appeared at 9.45 and 8.25 ppm belong to protons of COOH and phenolic OH groups, [35] respectively. The signal at 5.65 ppm corresponds to the -NH 2 protons.…”
Section: H and 13 C Nmr Spectra Of The Ligandmentioning
confidence: 99%